2018
DOI: 10.1021/acs.jpcc.8b01402
|View full text |Cite
|
Sign up to set email alerts
|

Study of C/Doped δ-Bi2O3 Redox Reactions by in Operando Synchrotron X-ray Diffraction: Bond Energy/Oxygen Vacancy and Reaction Kinetics Relationships

Abstract: One major technical and economic hurdle on the sequestration of CO2 is its separation from nitrogen when fossil fuels are burned in air. An alternative, thermodynamically equivalent approach is to use a metal oxide as an oxygen carrier (oxidizer) and then recycle the carrier following its reduction by exothermic reoxidation in air. This process, termed chemical looping combustion (CLC), places many requirements on the oxygen carrier. Here, we explore how to evaluate the relationship between the microscopic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Since the addition of metal promoters contributes to the distribution and concentration of oxygen vacancies, the vacancy effects are usually valued in the studies of mixed metal OCs. Zachariah et al 9 reported that the activation energy and the reaction rate of carbon doped with δ-Bi 2 O 3 were improved due to a high oxygen vacancy concentration of the doped Bi 2 O 3 . Fan et al 10 showed that Li doping-induced oxygen vacancies would benefit the adsorption of methyl radicals while suppressing the C−H decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Since the addition of metal promoters contributes to the distribution and concentration of oxygen vacancies, the vacancy effects are usually valued in the studies of mixed metal OCs. Zachariah et al 9 reported that the activation energy and the reaction rate of carbon doped with δ-Bi 2 O 3 were improved due to a high oxygen vacancy concentration of the doped Bi 2 O 3 . Fan et al 10 showed that Li doping-induced oxygen vacancies would benefit the adsorption of methyl radicals while suppressing the C−H decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…11 In papers that extend beyond traditional notions of combustion, there are those that describe work on catalyzed combustion of methane 12 and toluene 13 and solid-state oxygen sources for chemical looping combustion. 14 Finally, three of the publications in this Virtual Issue take up the subject of nanoparticle-enhanced combustion, investigating Al nanoparticles 15,16 and Ni-CeO x hybrid nanoparticles. 17 Theoretical papers also cover many topics, ranging from accurate 18,19 and approximate 20 studies of molecular properties, interaction potential energy surfaces, 21−23 transition state theory calculations of rate coefficients, 24 and master equation simulations 25 to sensitivity of kinetic models.…”
mentioning
confidence: 99%
“…In papers that extend beyond traditional notions of combustion, there are those that describe work on catalyzed combustion of methane and toluene and solid-state oxygen sources for chemical looping combustion . Finally, three of the publications in this Virtual Issue take up the subject of nanoparticle-enhanced combustion, investigating Al nanoparticles , and Ni-CeO x hybrid nanoparticles …”
mentioning
confidence: 99%